Safety and immunogenicity of combinations of recombinant subtype E and B human immunodeficiency virus type 1 envelope glycoprotein 120 vaccines in healthy Thai adults - Pitisuttithum P. (2014)
Safety and immunogenicity of 2 recombinant human immunodeficiency virus (HIV) type 1 envelope glycoprotein (gp) 120 vaccines derived from SF2 (subtype B) and CM235 (CRF01_AE, Thai E) were evaluated in 370 Thai adults at low risk of HIV infection. Various doses of CM235 (25, 50, or 100 μg) and SF2 (0, 25, or 50 μg) gp120 were used. Eighty volunteers received placebo. There were no serious adverse events related to vaccination. Binding antibody developed in all vaccine recipients. There was no dose response to CM235 gp120, but a dose response to gp120 SF2 was present. Neutralizing antibodies to subtype E HIV-1 NPO3 and subtype B HIV-1 SF2 developed in 84% and 82% of vaccine recipients, respectively. Lymphoproliferative responses were detected in >95% of vaccine recipients. There was no evidence of antigenic interference in HIV-specific humoral or cellular responses. The gp120 Thai E and SF2 vaccines were safe and immunogenic in combination and could be advanced into phase 3 testing.